2023
DOI: 10.3389/fimmu.2023.1120519
|View full text |Cite
|
Sign up to set email alerts
|

Emerging insights into the role of ferroptosis in the pathogenesis of autoimmune diseases

Abstract: Ferroptosis, a novel type of regulated cell death mediated by iron-dependent lipid oxidation, was discovered a decade ago. Significant progress has been made in our knowledge of ferroptosis and immune dysfunction. This review covers recent advancements in the interaction of ferroptosis and the immune system, with an emphasis on autoimmune diseases. The critical regulators of ferroptosis are summarized in the context of reactive oxygen species biology, lipid metabolism, and iron homeostasis. The molecular cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 162 publications
0
3
0
Order By: Relevance
“…Recently, the role of ferroptosis in autoimmune diseases has been reviewed. Fan et al ( 11 ) highlighted crosstalk between ferroptosis and different immune cells and discussed the role of ferroptosis in autoimmune disease and Lai et al ( 10 ) also discussed how ferroptosis contributes to the pathogenesis of SLE, RA and IBD. However, the autoimmune diseases included in the aforementioned reviews are relatively limited and did not summarize the association between ferroptosis and autoimmune response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of ferroptosis in autoimmune diseases has been reviewed. Fan et al ( 11 ) highlighted crosstalk between ferroptosis and different immune cells and discussed the role of ferroptosis in autoimmune disease and Lai et al ( 10 ) also discussed how ferroptosis contributes to the pathogenesis of SLE, RA and IBD. However, the autoimmune diseases included in the aforementioned reviews are relatively limited and did not summarize the association between ferroptosis and autoimmune response.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study of ferroptosis offers a fresh vantage point for investigating these conditions, introducing a novel perspective into the realm of autoimmune disease research. One of the contributing factors to the development of autoimmunity is the aberrant initiation of cell death and inadequate clearance of deceased cells, leading to the exposure or release of intracellular contents that activate the immune system [ 624 ]. Ferroptosis plays a substantial role in influencing both the quantity and functionality of immune cells625.…”
Section: Ferroptosis In Pathologiesmentioning
confidence: 99%
“…The accumulation of ROS and lipid peroxides promotes tissue damage and bacterial dissemination, whereas HO-1 increases the levels of ferrous metals, contributing to Mtb survival [ 154 ]. Additionally, regulating ferritin and ferroportin by HO-1 can reduce intracellular oxidative stress and promote iron exit from the intracellular environment through the ferroportin protein [ 155 , 158 ]. Qiang et al showed that PtpA triggers ferroptosis to promote Mtb pathogenicity and dissemination.…”
Section: Cell Death Mechanisms Activated By Mtb Virulence Factors: Th...mentioning
confidence: 99%